Against Plagiarism A Guide for Editors and Authors - Zhang, Yuehong (Helen).; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This is the first volume of a book series dedicated to "Qualitative and Quantitative Analysis of Scientific and Scholarly Communication". Fighting plagiarism is a the top priority for STM publishing. A practical guide will importantly contribute to the awareness of the relevant communities, bringing to the surface the basic rules and examples from the literature.
Part 1 - General plagiarism issues -- What is plagiarism? -- Differences between Anglophone and non-Anglophone journals -- Publication in more than one language -- How not to deal with it: a case study -- Part 2 - Discipline-specific plagiarism issues -- Biosciences: Replication of Methods sections -- Computing and Electrical & Electronic Engineering: republication of conference papers -- Part 3 - What to do about it -- Promoting awareness of publication ethics -- Avoiding plagiarism as an author -- Detecting potential plagiarism -- Dealing with plagiarism as an editor.
Keywords: Printing; Ethics; Science -- Study and teaching; Communication Studies